Terrorism and the Stock Market: A Case Study for Turkey Using STR Models - Eruygur, Ayegül Çorakçi; Omay, Tolga (Journal of Reviews on Global Economics, 2014)
Several attempts have been made in the literature to analyze the detrimental effects of terrorist activities on the stock market. However, in neither of these studies the effects of terrorist activities on stock returns are investigated through employing nonlinear models in spite of the fact that most financial data is shown to exhibit nonlinear behaviour. This study, therefore, aims to contribute to this growing area of research by exploring the potential nonlinear effects of terrorist activities on stock returns by employing smooth transition regression (STR) models. Our results show that terrorism has a statistically significant negative effect on the stock index when the intensity of terrorist activities passes a certain threshold level. This negative effect continues for terrorist activities below this threshold level, but becomes statistically insignificant. This study by conducting the analysis within a nonlinear framework offers important insights into the investors who want to make portfolio diversification strategies against terrorism risk.